Recuperated power cycle analysis model: Investigation and optimisation of low-to-moderate resource temperature Organic Rankine Cycles - de M. Ventura, Carlos A.; Rowlands, Andrew S. (Energy (Oxford), 2015)
A numerical model for recuperated power cycles for renewable power applications is described in the present paper. The original code was written in Python and results for a wide range of working fluids and operating point conditions are presented. Here, the model is applied to subcritical and transcritical Rankine cycles. It comprises a brute-force search algorithm that covers a wide parametric study combining working fluid, resource and cooling temperatures as well as high-side pressures in order to ascertain the best working fluid for a given resource temperature and operating point. The present study determined the fluids that maximise the specific energy production from a hot stream for a range of low-to-medium temperature (100–250 °C) resources. This study shows that for the following resource temperatures: 100 °C, 120 °C, 150 °C, 180 °C and 210 °C, R125, R143a, RC318, R236ea and R152a were found to maximise specific energy production, respectively. In general, the inclusion of a recuperator within the power cycle results in greater specific energy production for a given operating temperature. However, it was found that for all fluids there was a threshold pressure above which the inclusion of a recuperator did not enhance system performance. This may have design and economic ramifications when designing next-generation transcritical and supercritical power cycles. •We investigated recuperated cycle configurations for 21 working fluids.•We performed a parametric analysis on resource temperature and operating pressure.•We report the rank of various working fluids for the cycle conditions specified.•Using a recuperator allows for greater performance at lower high-side pressures.•Some fluids are more tolerant to resource temperature variations than others.